Influence of co doping on structural and band gap energy properties of ZnO based varistor ceramic - Ting, Lee Mon; Ismail, Nur Quratul Aini; Sa’at, Nor Kamilah; Azis, Raba'ah Syahidah; Mohd Zaid, Mohd Hafiz (Universitas Negeri Surabaya, 2022)
Photopyroelectric (PPE) technique has been widely used in applied science and technology fields including the study of materials in thermal and optical properties. The sample, Zn1-xCox (x= 0.4, 0.8, 1.2, 1.6, 2.0 wt%) was prepared using solid state method sintered at 1200 ͦC to study the effect of concentration on the energy band gap (Eg). XRD, SEM with EDX analysis were used to characterise the materials' structure, morphology, and density. The PPE setup is used to determine band gap energy (Eg) values. The Eg shows the decreasing trend when the concentration of CoO increases